Never Ending Analysis of a Century Old Evolutionary Debate: “Unringing” the Urmetazoon Bell - Schierwater, Bernd; Holland, Peter W. H.; Miller, David J.; Stadler, Peter F.; Wiegmann, Brian M.; Wörheide, Gert; Wray, Gregory A.; DeSalle, Rob (Frontiers in Ecology and Evolution, 2016)
Our understanding of the early evolution of animals will be greatly improved if a final solution can be found to the evolutionary relationships between Porifera, Placozoa, Ctenophora, Cnidaria and Bilateria. There have been many recent attempts to solve this key issue at the base of the metazoan tree of life, and these have sparked heated discussions and highlighted fundamental analytical problems. We argue that solving this problem will necessitate analysis of disparate data types, including phylogenomic data, larger scale genomic characters, developmental data and morphological characters. At the least, morphological and developmental data must be used to cross-validate phylogenomic conclusions, but ideally solutions should be sought to the problems of combining disparate data sources with appropriate character weighting and algorithm choice.